Intratumoral HPV16-specific T cells constitute a type I-oriented tumor microenvironment to improve survival in HPV16-driven oropharyngeal cancer - Welters, Marij J. P.; Charoentong, Pornpimol (Clinical cancer research, 2018)
Purpose: Human papillomavirus (HPV)-associated oropharyngeal squamous cell cancer (OPSCC) has a much better prognosis than HPV-negative OPSCC, and this is linked to dense tumor immune infiltration. As the viral antigens may trigger potent immunity, we studied the relationship between the presence of intratumoral HPV-specific T-cell responses, the immune contexture in the tumor microenvironment, and clinical outcome.Experimental Design: To this purpose, an in-depth analysis of tumor-infiltrating immune cells in a prospective cohort of 97 patients with HPV16-positive and HPV16-negative OPSCC was performed using functional T-cell assays, mass cytometry (CyTOF), flow cytometry, and fluorescent immunostaining of tumor tissues. Key findings were validated in a cohort of 75 patients with HPV16-positive OPSCC present in the publicly available The Cancer Genome Atlas database.Results: In 64% of the HPV16-positive tumors, type I HPV16-specific T cells were present. Their presence was not only strongly related to a better overall survival, a smaller tumor size, and less lymph node metastases but also to a type I-oriented tumor microenvironment, including high numbers of activated CD161+ T cells, CD103+ tissue-resident T cells, dendritic cells (DC), and DC-like macrophages.Conclusions: The viral antigens trigger a tumor-specific T-cell response that shapes a favorable immune contexture for the response to standard therapy. Hence, reinforcement of HPV16-specific T-cell reactivity is expected to boost this process. Clin Cancer Res; 24(3); 634-47. ©2017 AACRSee related commentary by Laban and Hoffmann, p. 505.
Published Online First: October 10, 2017
Gesehen am 02.07.2019